2020
DOI: 10.1017/jsi.2020.3
|View full text |Cite
|
Sign up to set email alerts
|

Screencast-Delivered Professional Development Targeting Teachers’ Self-Efficacy and Beginning-of-the-Year Classroom Management Practices

Abstract: Classroom management remains one of the greatest challenges for teachers. In this study, with 52 general and special education teachers, we examined the effectiveness of a screencast-delivered professional development program focused on classroom management practices in the first 3 days of school. Results suggest that after participating in the program, teachers report a positive change to the start of their school year across 12 different areas. Further, teachers’ classroom management self-efficacy increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In the most recent study, researchers found that among a sample of 64 special educators serving a variety of students with disabilities, behavior management efficacy had a strong inverse relationship to burnout (d = −0.85 to −1.20; . Given these preliminary results, and the notion that behavior management is a malleable factor that can be addressed during preservice and inservice training (Garwood et al, 2017), examining special educators' efficacy for behavior management is necessary.…”
Section: Efficacy For Behavior Managementmentioning
confidence: 99%
“…In the most recent study, researchers found that among a sample of 64 special educators serving a variety of students with disabilities, behavior management efficacy had a strong inverse relationship to burnout (d = −0.85 to −1.20; . Given these preliminary results, and the notion that behavior management is a malleable factor that can be addressed during preservice and inservice training (Garwood et al, 2017), examining special educators' efficacy for behavior management is necessary.…”
Section: Efficacy For Behavior Managementmentioning
confidence: 99%
“…BEST in CLASS may influence teacher burnout through several hypothesized mechanisms (Garwood, 2022). One mechanism highlighted by Garwood and Harris (2020) and others (e.g., Aloe et al, 2014) is teaching efficacy. Teaching efficacy represents a teachers’ confidence in their abilities to manage student behavior and engagement and their belief that they can have a positive effect on students’ desirable behavior and achievement (Han & Weiss, 2005).…”
Section: Best In Class Teacher Burnout and Fidelity Of Implementationmentioning
confidence: 99%